2018
DOI: 10.1103/physrevb.97.094517
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid drag in the two-component Bose-Hubbard model

Abstract: In multicomponent superfluids and superconductors, co-and counter-flows of components have in general different properties. It was discussed in 1975 by Andreev and Bashkin, in the context of He 3 /He 4 superfluid mixtures, that inter-particle interactions produce a dissipationless drag. The drag can be understood as a superflow of one component induced by phase gradients of the other component. Importantly the drag can be both positive (entrainment) and negative (counter-flow). The effect is known to be of cru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 68 publications
(101 reference statements)
4
53
0
Order By: Relevance
“…Within an experimental cycle of less than 20 s, we produce stable dual-species BECs with more than 10 5 atoms and tunable species population imbalance. This result represents a convenient starting point for future studies on mass-imbalanced superfluid mixtures with tunable interactions which are expected to exhibit exotic phenomena such as the formation of unusual vortex structures [56,57], self-bound states [58] and non-dissipative drag effects [1,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…Within an experimental cycle of less than 20 s, we produce stable dual-species BECs with more than 10 5 atoms and tunable species population imbalance. This result represents a convenient starting point for future studies on mass-imbalanced superfluid mixtures with tunable interactions which are expected to exhibit exotic phenomena such as the formation of unusual vortex structures [56,57], self-bound states [58] and non-dissipative drag effects [1,[59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…The winding number W i is a a topological quantity, for a system with periodic spatial boundary conditions, counting the net number of times the particle trajectories wind around the system in direction i. In the multicomponent case, following the derivation of Ref [23], the drag is given by…”
Section: Beyond Weak-coupling Mean-field Theory: Quantum Monte Carmentioning
confidence: 99%
“…In the condensed matter context, the effect became of great interest with the advent of optical lattices, which allow for a precise control of strongly correlated superfluids [14,15]. The strength of the Andreev-Bashkin drag is controlled by the optical lattice parameters in combination with on-site interactions [16]. It was shown that the effect, in relative terms, can be arbitrarily strong and that the Andreev-Bashkin drag-coefficient ρ ab can also become negative.…”
mentioning
confidence: 99%
“…In the latter case, one deals with a counterflow, where the flow of one component generates a mass flow of the other component in the opposite direc-tion [8][9][10][11]. It was pointed out that the effect should lead to formation of new superfluid states where only dissipationless co-flow (paired superfluids) or only counterflow (supercounterfluids) can exist [8][9][10][11][12][13][16][17][18]. At the same time even relatively weak drag substantially changes rotational responses [19,20].…”
mentioning
confidence: 99%